The Effect of Body Mass Index on Fluoroscopic Time and Radiation Dose During Sacroiliac Joint Injections. Issue 8 (22nd November 2015) - Cushman, Daniel; Flis, Alexandra; Jensen, Ben; McCormick, Zachary
Abstract: Background: Sacroiliac joint (SIJ) injections are commonly performed under fluoroscopic guidance. Radiation exposure to patients and providers has not been comprehensively studied, particularly the effect of body mass index (BMI). Objective: To identify whether patients with a larger BMI require longer fluoroscopy time or a larger radiation dose during performance of an SIJ injection. Design: Retrospective study of an academic institution database. Setting: Academic outpatient musculoskeletal clinic. Patients: All patients who underwent SIJ injections during a 10‐year period. Main Outcome Measurements: Machine‐reported fluoroscopic time and machine‐reported radiation dose. A Bonferroni correction was implemented with P ≤ .01 as statistically significant. Results: A total of 453 SIJ injections were performed in 359 patients. No statistically significant differences in fluoroscopy time were found between patients with BMI scores identified as normal, overweight, and obese ( P = .054). However, the radiation doses were significantly greater for patients with higher BMI scores (χ 2 [2, n = 441] = 62.4, P < .001); the median (interquartile range) doses were 1210 (839), 1671 (1240), and 2090 (2170) mGy‐cm 2 for normal weight, overweight, and obese patients, respectively. Although longer needles were used more often in obese patients (χ 2 [2, n = 452] = 31.5, P < .001), fluoroscopy time was not associated with needle length ( P = .162). No relationships were identified between fluoroscopy time and first‐time (as opposed to repeat) injection ( P = .123), trainee involvement (χ 2 [1, n = 698] = 3.9, P = .049), or age ( P = .337). Conclusions: Patients with an elevated BMI score who are undergoing SIJ injection receive an increased radiation dose despite equivalent fluoroscopic time. This finding suggests that the increased dose is likely due to x‐ray output from the fluoroscope traversing a greater tissue mass, as opposed to the physician requiring more fluoroscopic images for proper needle placement. Fortunately, the increased radiation dose delivered to patients with a larger BMI score likely has negligible effects.